(untitled) (Advancements in Homeopathic Research, 2022)
Introduction- Folliculitis barbae (FB) is confined to inflammation of the hair follicles in the beard area; it is due to infection with the Staphylococcus aureus. Homoeopathy provides a better response in FB, and one such type of case report is presented here. Diagnosis & treatment- Here patient complaining of acute allergic contact dermatitis symptoms in beard area with history of using old shaving equipment, later diagnosed as FB. On holistic approach and individualization Rhus toxicodendron was selected as Homoeopathic similimum. Within fifteen days of homoeopathic treatment, improvement has been observed in patient with FB with all aspect. Conclusion- This case report suggests that homoeopathic intervention may be the treatment for the alleviation of presenting symptoms of FB.